Study o Safety and Shelflife of Red Chili Paste - Rosaria .; Winiati P Rahayu (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2008)
Red chili is an important food ingredient which may not be always self, when obtained from the market. The aims of the study was to evaluate the safety and shelf life of red chili paste. Based on survey conducted with 20 vendors in Bogor, we found red chili paste in generally composed of red chili, water, and NaCl. About 75% of the vendors claimed that their red chili paste not sold in the first market day is stored in a plastic container at room temperature and resold for the next day. They claimed that their red chili paste can be stored for 2-8 days. The red chili paste showed moisture content of 71.6-86.8% (w/wb), pH 4.7-6.9% (w/w). About 33.3% of them positively contained excessive amount of sodium benzoate and 36% of them contained Rhodamin B which is prohibited as food coloring. From the microbiological side, the red chili paste contained 9.5 x 10 3 - 3.8 x 105cfu/g mould and yeast; 1.2 x 103 - 5.6 x 104 cfu/f spore forming bacteria; 5.2 x 102- 1.2 x 104 cfu/g S. aureus;